2020
DOI: 10.7554/elife.57457
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic genetic variation revealed in diverse Hsp104 homologs

Abstract: The AAA+ protein disaggregase, Hsp104, increases fitness under stress by reversing stress-induced protein aggregation. Natural Hsp104 variants might exist with enhanced, selective activity against neurodegenerative disease substrates. However, natural Hsp104 variation remains largely unexplored. Here, we screened a cross-kingdom collection of Hsp104 homologs in yeast proteotoxicity models. Prokaryotic ClpG reduced TDP-43, FUS, and α-synuclein toxicity, whereas prokaryotic ClpB and hyperactive variants were ine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 140 publications
(272 reference statements)
1
19
0
Order By: Relevance
“…Conversely, the demonstrated ability of tLST-encoded proteins to prevent protein aggregation, or to restore aggregated proteins to their native state may be an asset in biotechnological applications that aim to achieve high-yield production of heterologously expressed proteins ( Guzzo, 2012 ). Those characteristics might be extended to clinical applications as ClpG also prevents toxicity of protein substrates involved in neurogenerative diseases ( March et al, 2020 ). Moreover, while core genome heat shock proteins are often essential genes, tLST encoded heat shock proteins are accessory genes and thus provide an excellent tool to study the role of protein homeostasis in bacterial stress resistance and ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the demonstrated ability of tLST-encoded proteins to prevent protein aggregation, or to restore aggregated proteins to their native state may be an asset in biotechnological applications that aim to achieve high-yield production of heterologously expressed proteins ( Guzzo, 2012 ). Those characteristics might be extended to clinical applications as ClpG also prevents toxicity of protein substrates involved in neurogenerative diseases ( March et al, 2020 ). Moreover, while core genome heat shock proteins are often essential genes, tLST encoded heat shock proteins are accessory genes and thus provide an excellent tool to study the role of protein homeostasis in bacterial stress resistance and ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, potentiated Hsp104 variants have been generated by engineering an autoregulatory domain ( Jackrel and Shorter, 2015 ). These enhanced Hsp104 variants can rescue toxicity caused by α-synuclein, FUS and TDP-43 in yeast, Caenorhabditis elegans and mammalian cell model systems ( Jackrel et al, 2014 ; Mack et al, 2020 preprint; March et al, 2020 ; Yasuda et al, 2017 ).
Fig.
…”
Section: Hsp104mentioning
confidence: 99%
“…Our group has also recently described natural Hsp104 variants that rescue the toxicity of α-synuclein and TDP-43 in an ATPase-independent manner ( March et al, 2020 ). In this study, March et al surveyed the natural sequence space of homologous Hsp104 proteins and found that Hsp104 proteins from diverse species can selectively chaperone α-synuclein in yeast and C. elegans , or TDP-43 in yeast and human cells, without off-target toxicity ( March et al, 2020 ). These naturally enhanced variants did not display enhanced disaggregase activity in vitro , nor did they stringently require ATP binding and hydrolysis to rescue proteotoxicity in yeast.…”
Section: Hsp104mentioning
confidence: 99%
See 1 more Smart Citation
“…Although metazoans lack an Hsp104 homolog, it was hypothesized that Hsp104 might be active against proteins that aggregate in human disease due to the conserved fold of amyloid and prion-like proteins. While activity of Hsp104 against many human disease-associated proteins is weak, potentiated variants of Hsp104 have been engineered that can prevent and reverse the misfolding of diverse proteins including TDP-43, FUS, and α-Syn [198][199][200][201][202][203][204][205][206][207][208][209][210][211]. Potentiated Hsp104 variants also displayed therapeutic activity in worm and mammalian cell models of neurodegenerative disease [198,212,213].…”
Section: Protein Chaperones To Counter Aberrant Phase Transitionsmentioning
confidence: 99%